Abdominal Stretching Exercise Menurunkan Intensitas Dismenorea Pada Remaja Putri - yuanita syaiful; Siti Varyal Naftalin (Akademi Keperawatan Dharma Husada Kediri, 2018)
Dysmenorrhea is a menstrual disorder with complaints of pain or cramps in the lower abdomen during menstruation that can be experienced by some women. Abdominal Stretching Exercise is a stretching exercise for the abdominal muscles that can reduce the intensity of menstrual pain. The purpose of this study is to determine the effect of Abdominal Strength Training Exercise on the intensity of pain during menstruation (Dismenorrhea) in adolescent girls. The research methode used pre-experimental (one group pre test-post design). The population involved in this study were 30 students of SMK Dharma Wanita Gresik, with a samples size of 28 respondents using purposive sampling. Independent variable in this study is the Abdominal Strength Exercise and dependent variable of this study is the intensity of dimenorrhea pain. Instrument of this study were the operational standard of the Abdominal Stretching Exercise procedure was prepared by researchers based on the principles of Thermacare and Questionnaire sheet and observation of the intensity of pain in the Bourbanis scale. Datawere analized using wilcoxon sign rank test. The results obtained mean before 2.50 and mean after 1.82, while standartd deviation before 0,509 and standart deviation after 0,612. The results of the Wilcoxon statistical test with a sig (2-tailed) p = 0.000 which means (αcount)) ≤ 0, 05 which means that there is an influence of Abdominal stretching Exercise on the intensity of dysmenorrhea in adolescent girl. Abdominal stretching exercise carried out 3 days before menstruation with a duration of 30 minutes can affect the intensity of dysmenorrhea so that it can be applied in providing comprehensive nursing care for adolescent girl who experience dysmenorrhea.